Pengaruh Blended Learning Berbasis Elektronik Modul pada Materi Ekosistem Terhadap Motivasi Belajar Siswa Di MA NU Mazro’atul Huda Karanganyar Demak - Andi Asyhari; Aulia Rahmawati (Program Studi Pendidikan Biologi Fakultas Keguruan dan Ilmu Pendidikan, 2021)
This study aims: 1) to determine the application of the electronic-based blended learning model to the Ecosystem material at MA NU Mazro'atul Huda Karanganyar Demak for the 2020/2021 academic year; 2) to find out how the level of student motivation at MA NU Mazro'atul Huda Karanganyar Demak for the 2020/2021 academic year; 3) to determine the level of influence of Electronic-Based Blended Learning Modules on Ecosystem Materials on Student Learning Motivation at MA NU Mazro'atul Huda Karanganyar Demak for the 2020/2021 academic year. The method used is a quantitative method with the type of research Pre-Experimental Designs in the form of Intact-Group Comparison. The population in this study were students of class X IPA which consisted of 2 classes. Then the two classes were sampled using a non-probability sampling technique with saturated sampling type. Then the data was collected using a questionnaire and documentation. The data analysis method used is descriptive analysis and inferential statistics using t test. The results showed that there was a positive effect on electronic module-based blended learning on students' learning motivation, as evidenced by the hypothesis testing data using the Independent T-Test, the t-count value was 2.749 and the t-table value was 2.002. Because the mean t arithmetic > t table (2.749 > 2.002), or the value of t arithmetic = 2.749 lies outside the range -2.002 to +2.002. Thus, Ho is rejected and Ha is accepted, meaning that there is a difference between the average learning motivation of the experimental and control classes. Thus, there is an influence of the electronic module-based Blended Learning learning model on students' learning motivation.